The Relationship Between Empowering Motivational Climate in Physical Education and Social Adaptation of Senior High School Students: An Analysis of Chain Mediating Effect - Guo, Kelei; Ma, Qishuai; Yao, Shujun; Liu, Chao; Hui, Zhen; Chen, HuaSheng; Wen, Pengfei (Frontiers in Psychology, 2022)
This study aims to contribute to understanding the mechanisms underlying the association between empowering motivational climate in physical education and social adaptation among senior high school students, and has important implications for interventions which aim at improving social adaptation among senior high school students. Through the quota sampling, 1526 students (average age=17 years, SD=0.714 years) who came from Anhui Province and met the requirements participated and completed the Empowering Motivational Climate Questionnaire in Physical Education(EMCQ-PE), the Physical Education Engagement Scale(PEES-S), the Emotional Intelligence Scale (EIS) (Chinese version) and the Adolescent Social Adaptation Assessment Questionnaire (ASAAQ). For data analysis, Pearson’s correlation analysis, structural equation model test, and bias-corrected percentile Bootstrap method were carried out in turn. The results showed that empowering motivational climate in physical education positively predicted social adaptation (β=0.282, p＜0.01), empowering motivational climate in physical education positively predicted physical education engagement and emotional intelligence (β=0.169, p＜0.01; β=0.690, p＜0.01), physical education engagement positively predicted emotional intelligence and social adaptation (β=0.591, p＜0.01; β=0.058, p＜0.05), emotional intelligence positively predicted social adaptation (β=0.365, p＜0. 01). Physical education engagement and emotional intelligence played a mediating role between empowering motivational climate in physical education and social adaptation, with a total mediating effect value of 0.251. The present studies show that empowering motivational climate in physical education not only directly predicts social adaptation, but also indirectly predicts social adaptation through the chain mediating effect of physical education engagement and emotional intelligence.